Computer-assisted education and application in the music flipped classroom: a review of the literature - Qisen, Zhu; Jamaludin, Khairul Azhar; Mohamad Nasri, Nurfaradilla; Jinglong, Li (Learning Gate, 2024)
The application of computer-assisted learning in music education not only changes the traditional teaching mode, in addition, it provides students with a richer and more personalized learning experience. However, the implementation of computer-assisted learning also faces many challenges, such as insufficient technological infrastructure, teachers' role change, and the development of students' independent learning ability. Therefore, this study explored the pedagogical effects of computer-assisted learning applications in music-flipped classrooms and how to enhance students' learning and musical expression through a computer-assisted flipped classroom teaching model by using the literature review method. Through a five-step approach, this study analyzes the current status, problems, challenges and opportunities of computer-assisted education in music-flipped classrooms, aiming to assess its effectiveness and propose strategies to promote innovation and development in music education. The study findings demonstrated that utilising computer-assisted learning in the music-flipped classroom substantially enhanced students' musical knowledge, skills, and performance by fostering active learning participation and interaction. Conclusions drawn from the study found that computer-assisted learning is effective in improving learning outcomes and musical performance and can contribute to the advancement of music education theory and practice. Future academic exploration needs to confront these obstacles and delve into inventive applications of computer-assisted learning. Furthermore, there is a necessity for prolonged investigations to evaluate the enduring influence of music education outcomes through computer-assisted music-flipped classroom instruction.